Fa’āliyyah Ittikhād Manhaj al-Makālamah wa al-Mabāhaṡah fī Tahqīq Ta’allum al-Balāgah bi al-Ma’had - Ika Pramesti; Kunti Nadiyah Salma; Wahyu Hanafi Putra (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study was to test the effectiveness of using the calling and discussion method in improving Balagah's learning abilities. This research is quantitative with demographic analysis, and the subject of the study is all students from the fifth semester. Its model is the students from the fifth B semester with a total of 19 students—data collection by questionnaire, observation, and documentation. Furthermore, they were then analyzed by the